68Ga-PSMA-PET/CT for the evaluation of liver metastases in patients with prostate cancer - Damjanovic, Jonathan; Janssen, Jan-Carlo; Prasad, Vikas; Diederichs, Gerd; Walter, Thula; Brenner, Winfried; Makowski, Marcus R. (Cancer Imaging, 2019)
Background: The purpose of this study was to evaluate the imaging properties of hepatic metastases in 68Ga-PSMA positron emission tomography (PET) in patients with prostate cancer (PC). Methods: 68Ga-PSMA-PET/CT scans of PC patients available in our database were evaluated retrospectively for liver metastases. Metastases were identified using 68Ga-PSMA-PET, CT, MRI and follow-up scans. Different parameters including, maximum standardized uptake values (SUVmax) of the healthy liver and liver metastases were assessed by two- and three-dimensional regions of interest (2D/3D ROI). Results: One hundred three liver metastases in 18 of 739 PC patients were identified. In total, 80 PSMA-positive (77.7%) and 23 PSMA-negative (22.3%) metastases were identified. The mean SUVmax of PSMA-positive liver metastases was significantly higher than that of the normal liver tissue in both 2D and 3D ROI (p ≤ 0.05). The mean SUVmax of PSMA-positive metastases was 9.84 ± 4.94 in 2D ROI and 10.27 ± 5.28 in 3D ROI; the mean SUVmax of PSMA-negative metastases was 3.25 ± 1.81 in 2D ROI and 3.40 ± 1.78 in 3D ROI, and significantly lower than that of the normal liver tissue (p ≤ 0.05). A significant (p ≤ 0.05) correlation between SUVmax in PSMA-positive liver metastases and both size (ρSpearman = 0.57) of metastases and PSA serum level (ρSpearman = 0.60) was found. Conclusions: In 68Ga-PSMA-PET, the majority of liver metastases highly overexpress PSMA and is therefore directly detectable. For the analysis of PET images, it has to be taken into account that also a significant portion of metastases can only be detected indirectly, as these metastases are PSMA-negative.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Liver metastasis; PET/CT; Prostate cancer; PSMA